1985
DOI: 10.1111/j.1600-0773.1985.tb00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiography of l–Methyl–4–phenyl–l,2,3,6–tetrahydropyridine (MPTP): Uptake in the Monoaminergic Pathways and in Melanin Containing Tissues

Abstract: A recently discovered neurotoxic compound, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, has been found to cause a parkinsonian-like syndrome in man and monkey, but not in laboratory animals such as rat, mouse and guinea pig. MPTP seems to selectively destroy the melanin containing dopaminergic cells in pars compacta of substantia nigra. Lower mammalian species do not have melanin in these cells, which indicates that the presence of neuromelanin may be of importance for the development of MPTP-induced lesions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Although the liver, kidneys, and brain contained the highest levels of radioactivity at the end of the scintigraphic study, a progressive accumulation of radioactivity was observed within the eyes over the course of the imaging study. Accumulation within this organ was evident within 50 min postinjection; such accumulation has been reported by other groups using radiolabeled MPTP in the monkey (Hartvig et al, 1986) and is presumed to reflect high retinal MA0 activity and trapping of metabolites by melanin-containing dopaminergic neurons of the retina (D'Amato et al, 1987;Lyden et al, 1985). In contrast to the rodent heart, which maintains levels of [ 1251]MHTP-derived radioactivity comparable to those of the brain (Efange et al, 1989), very little radioactivity was retained in the monkey heart.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Although the liver, kidneys, and brain contained the highest levels of radioactivity at the end of the scintigraphic study, a progressive accumulation of radioactivity was observed within the eyes over the course of the imaging study. Accumulation within this organ was evident within 50 min postinjection; such accumulation has been reported by other groups using radiolabeled MPTP in the monkey (Hartvig et al, 1986) and is presumed to reflect high retinal MA0 activity and trapping of metabolites by melanin-containing dopaminergic neurons of the retina (D'Amato et al, 1987;Lyden et al, 1985). In contrast to the rodent heart, which maintains levels of [ 1251]MHTP-derived radioactivity comparable to those of the brain (Efange et al, 1989), very little radioactivity was retained in the monkey heart.…”
Section: Resultssupporting
confidence: 59%
“…However, the selective dopaminergic neurotoxicity of MPTP may be partially explained by the regional distribution of MPP in vivo. Following the administration of radiolabeled MPTP to rodents, high concentrations of radioactivity were found within the caudate-putamen, nucleus accumbens, and locus coeruleus (Lyden et al, 1985;Lyden-Sokolowski et al, 1988). These areas of the brain are known to contain the highest concentrations of catecholamine uptake sites (Javitch et al, 198513).…”
Section: Introductionmentioning
confidence: 99%
“…The substance was ultimately purified and demonstrated to bind to melanin (25). The substance produces Parkinson-like symptoms in animals but only in those species that contain high levels of neuromelanin in the substantia nigra (26). It also preferentially kills melanoma cells containing high levels of melanins (27).…”
Section: Fifth Blind Person: "I Know What Melanin Does! It Binds To Dmentioning
confidence: 99%
“…Additionally, decreased concentration of corticotropin-releasing factor, found in PD patients, was also recorded in amygdala and paraventricular nucleus of hypothalamus in MPTP-treated rats (Huang and Lee 1995). Significant loss of DA and 5-hydroxytryptamine (serotonin) was recorded in amygdala along with striatum, (Lyden et al 1985) Altered glucose metabolism in spinal cord (Schwartzman and Alexander 1985) Presence of MPTP metabolizing system in spinal cord (Samantaray et al 2008b) Neurodegeneration in cervical and lumbar spinal cord neurons (Samantaray et al 2008a,b) Upregulation of calpain expression and activity in spinal neural cells (Ray et al 2000;Chera et al 2002Chera et al , 2004 Acupuncture at GB34 and LR3 acupoints altered gene expression in cervical spinal cord (Choi et al 2011) Alpha-synuclein pathology and astrogliosis with progressive loss of locomotor function (Neumann et al 2002) Extensive immunoreactivity for insoluble phosphorylated on serine 129 isoform of alpha-synuclein and ubiquitin, associated with caspase 9 activation in spinal cord of end-stage symptomatic A30P mice. Parkin deficiency mitigated neuritic pathology in end-stage symptomatic A30P mice (Fournier et al 2009) Dopamine transporter knock-out Epidural electrical stimulation of dorsal column in spinal cord restored locomotion (Fuentes et al 2009(Fuentes et al , 2010…”
Section: )mentioning
confidence: 85%